(untitled) (Research, Society and Development, 2023)
Brazil is one of the countries with the greatest potential for fruit growing, being the world’s main producer and consumer of passion fruit. The study aimed to observe and report the management and production of sour yellow passion fruit through a localized irrigation system of a rural property in the municipality of Caririaçu – CE, and propose improvements in the production system. From the results obtained, it is possible to state that germination occurred in a sort time and that the passion fruit seedlings (Passiflora edulis. F. Deg.) achieved adequate performance for definitive cultivation in the field. Irrigation could have been better managed and that artificial pollination performed for the first time was fundamental for increasing productivity, the yield of pulp volume and diameters were satisfactory to serve the consumer market. Therefore, it can be concluded that productivity could have been higher if there had been correct irrigation management and if the fusarium attack had not occurred during the productive phase, which was only possible in just 6 months.